Present hedonism and future time perspectives predicting hypersexuality and problematic pornography use - Koós, Mónika; Orosz, Gábor; Demetrovics, Zsolt; Bőthe, Beáta (Frontiers in Psychiatry, 2022)
The Time Perspective (TP) theory (i.e., the psychological experience regarding time) was often examined in association with different addictive behaviors, and the different TPs (i.e., Past Positive, Past Negative, Present Hedonistic, Present Fatalistic and Future TPs) demonstrated different relationship patterns with them. However, most studies were conducted in relation to substance use-related disorders, leaving crucial knowledge gaps concerning the associations between TPs and potential behavioral addictions. The aim of the present study was to examine the associations between the five TP dimensions, hypersexuality, and problematic pornography use (PPU), considering potential gender differences. Participants from two independent samples (N1=554; N2=453) completed a self-report survey on TPs and sexual behaviors. Structural equation modeling results indicated that the Present Hedonistic TP had a positive, moderate, and the Future TP had a negative, weak association with hypersexuality in both samples. Only the Present Hedonistic TP had a significant, positive, weak-to-moderate association with PPU across the samples. The explained variances of the models were higher in case of hypersexuality (28% and 27%, respectively), than in case of PPU (1% and 14%, respectively). No significant gender differences were observed. In line with previous findings concerning other predictors of hypersexuality and PPU, the results of the present study suggest that hypersexuality and PPU may differ from each other in terms of their TP background. Yet, present hedonism, which is related to impulsivity, may play an important role in both problematic sexual behaviors, suggesting that interventions focusing on this TP might be successful in reducing hypersexuality and PPU.